2022
DOI: 10.1097/ijg.0000000000002098
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Trabeculotomy Failure in Primary Congenital Glaucoma

Abstract: Précis: This study demonstrates that a baseline corneal diameter >12.25, initial age <4 months at diagnosis, higher baseline IOP than 24 mm Hg, bilaterality, or inability to perform circumferential trabeculotomy, increases the risk of surgical failure of trabeculotomy in patients with primary congenital glaucoma (PCG). Purpose: The aim of this study was to identify clinical predictive factors for surgical failure and to evaluate potential prognostic factors affecting surgical success in patients with PCG who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A possible cause for the surgical failure to occur earlier in children with early-onset disease could be due to the fact that we have performed conventional trabeculotomy (probe) and not circumferential trabeculotomy (suture or catheter). The inability to perform circumferential suture trabeculotomy increases the risk of surgical failure in primary congenital glaucoma 24 . An increasing number of studies have demonstrated that ab externo Microcatheter-assisted trabeculotomy (MAT) or a 360-degree circumferential trabeculotomy is a more effective treatment than traditional rigid probe trabeculotomy for childhood glaucoma 25–27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible cause for the surgical failure to occur earlier in children with early-onset disease could be due to the fact that we have performed conventional trabeculotomy (probe) and not circumferential trabeculotomy (suture or catheter). The inability to perform circumferential suture trabeculotomy increases the risk of surgical failure in primary congenital glaucoma 24 . An increasing number of studies have demonstrated that ab externo Microcatheter-assisted trabeculotomy (MAT) or a 360-degree circumferential trabeculotomy is a more effective treatment than traditional rigid probe trabeculotomy for childhood glaucoma 25–27 .…”
Section: Discussionmentioning
confidence: 99%
“…The inability to perform circumferential suture trabeculotomy increases the risk of surgical failure in primary congenital glaucoma. 24 An increasing number of studies have demonstrated that ab externo Microcatheterassisted trabeculotomy (MAT) or a 360-degree circumferential trabeculotomy is a more effective treatment than traditional rigid probe trabeculotomy for childhood glaucoma. [25][26][27] Hu et al 28 recently showed that ab externo MAT had remarkably good outcomes as the primary therapy in their series of 13 eyes with early-onset glaucoma associated with SWS.…”
Section: Discussionmentioning
confidence: 99%